The Future of Internasional Marketing in the AI Era a Conceptual Review and Research - Stafani M.M; Miracle Robot; Miken Mandagi; Nistelrooy Wenas; Jonathan Kasenda; Risal Wuri; Wicliff Pangayow; Nathanael Kindangen; Darel Tolu; Rafli Pundoko (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2025)
Global digital technology developments have brought artificial intelligence (AI) as one of the most significant disruptive factors in marketing. According to Irvan Manggala et al. (2023), the implementation of AI in the era of the Industrial Revolution 5.0 has changed the paradigm of digital marketing through automation, real-time data analysis, and increased marketing strategy efficiency. This is in line with the findings of Labib (2024), who asserts that AI is revolutionizing the business landscape with six main clusters, namely AI-based market strategies, customer service, decision making, value transformation, psychosocial dynamics, and marketing ethics. Meanwhile, Nugroho & Sundari (2024) emphasize that AI not only increases productivity but also enables personalized customer journeys, consumer behavior predictions, and more adaptive pricing strategies. In the context of international marketing, Eteokleous, Leonidou, & Katsikeas (2016) remind us that AI integration must be balanced with corporate social responsibility (CSR) principles so that cross-border strategies do not only focus on profit but also meet global ethical demands. Thus, this study shows that the future of international marketing in the AI era will be marked by significant opportunities in efficiency, innovation, and personalization, but will also require regulation, transparency, and a balance between business interests and social sustainability.